Towards uniformity in the definition of acceptable mismatches for highly sensitized patients. (19th June 2019) - Chen, Mian; Zoet, Yvonne; Roelen, Dave; Martorell, Jaume; Middleton, Derek; Slavcev, Antonij; Iniotaki, Aliki; Claas, Frans; Fuggle, Susan
Abstract : The Eurotransplant (The Eurotransplant International Foundation) acceptable mismatch programme has been shown to be a successful tool to enhance transplantation of highly sensitized patients(HSPs). However, patients with rare HLA phenotypes in relation to the Eurotransplant donor population remain on the waiting list. EUROSTAM is an European Union funded project to explore the feasibility of a Europe‐wide acceptable mismatch programme enabling transplantation of HSPs with rare HLA phenotypes within their own organ exchange organization. The present study, which forms part of the EUROSTAM project, assesses the differences in the practices of the laboratories in different countries with respect to their HLA antibody profiling and risk adverseness. In the serum exchange exercises of 18 samples, a high level of variability has been shown in both assays and interpretation of results. In the data exchange exercise when all participants were given the same Luminex raw data for analysis, a high degree of consensus was reached where the median fluorescent intensity values of beads were <500 and >2000 for standard single antigen bead assays, or <500 and >5000 for assignment of acceptable mismatches. The risk adverseness analysis has showed distinct patterns of attitudes towards the perceived risks based on HLA antibody assay results, most probably influenced by the local protocols of the clinical transplant programme of each laboratory. In order to ensure fairness and maintain consistencies of organ exchange among partner transplant centres, a centralized facility will be instrumental for a uniform definition of acceptable mismatches.